Penentuan Wilayah Prioritas Penanganan Genangan di Kota Padang - Gilang Samudra; Ahyuni Ahyuni (JURUSAN GEOGRAFI FIS UNP, 2019)
Inundation is one of the problems faced in urban areas, one of which occurs in the Padang City with the main cause that is not functioning optimally the urban drainage system. To reduce waterlogged areas, it is necessary to determine priority areas for inundation management so that population activities are not disrupted and do not cause economic or environmental disruption. This study aims to determine 1) the potential for inundation in Padang City and 2) the priority area for inundation handling in Padang City. Potential inundation in Padang City was analyzed by a rational method that produced a prediction of surface runoff which was then overlaid with infiltration rate and drainage capacity. Priority areas will be handled first according to the results of the analysis of inundation potential using the AHP method with parameters referring to the Minister of Public Works Regulation 12/PRT/M/2014 concerning the Implementation of Drainage Systems. The results showed that 1) the potential for inundation in the Padang City occurs when the daily rainfall intensity with an average of 35.55 mm/hour produces a surface flow discharge with a discharge of 1.98 m3/second - 274.20 m3/second, while drainage is only able to accommodate the highest discharge of 127.37 m3/second there are even areas that do not have drainage systems, and low infiltration rates. The highest potential occurs in the Batang Arau watershed covering an area of ​​5730.04 Ha 2) Priority areas are scattered in each watershed in Padang City, where in the Air Dingin Watershed there are 3 sub-watersheds, Batang Arau watershed has 10 sub-watersheds, Batang Kandih watershed has 8 sub-watersheds, Batang Kuranji watershed has 8 sub-watersheds, Sungai Watershed Bananas have 2 sub-watersheds, and in Timbalun watershed there are 3 sub-watersheds which are priority areas for inundation management in areas of potential inundation. Whereas the priority areas for inundation management in the existing inundation area are the Batang Arau watershed with 3 sub-watersheds, Batang Kuranji watershed with 8 sub-watersheds, and Timbalun watershed with 2 sub-watersheds.